Analysis of Information Technology Service Management for Radio Frequency Spectrum Licensing Services at Balmon Palembang Using ITIL V3 - Andryani, Ade; Herdiansyah, Muhammad Izman; Negara, Edi Surya; Sutabri, Tata (International Journal of Artificial Intelligence Research, 2024)
This research discusses the importance of timely, accurate, and relevant information technology services to support organizational activities, particularly in the context of radio frequency spectrum licensing services. The lack of government oversight of IT services often leads to complaints, necessitating evaluation using the ITIL framework. The study seeks to examine how ITIL V3 processes are applied within radio frequency spectrum licensing services at Balmon Palembang through a qualitative descriptive method. Findings suggest that the services have implemented ITIL V3 processes with a maturity level at level 3 Defined.